The Influence of Rotating Direction on the Tribological Behavior of Grey Cast Iron with Curve Distributed Pit Textured Surface. (26th September 2017) - Sun, Shaoni; Xie, Liyang; Kelly, Peter; Long, Risheng; Li, Manhong; Feng, Jiling
Abstract : To investigate the influence of surface features, in the form of pits, on the wear resistance of grey cast iron (GCI), a finite element model of the pin-on-disc friction system, with pits distributed in a curved radial direction, was developed using APDL programming and the tribological behavior of textured surfaces was studied. The influence of relative rotation direction between the disc and the pin on the thermal behavior of the friction system under dry wear conditions was researched. GCI and C30E steel samples with pit textured surfaces were manufactured using laser marking equipment and tested using a tribology wear testing rig. The mass losses were measured and the worn surfaces were characterized. The influence of different rotation directions on the tribological behavior of the pit textured surfaces was also investigated. The simulation and test results revealed that rotation direction was a crucial parameter in determining the tribological behavior of surfaces with these features, regardless of the material. Under the conditions tested, when the pin rotated anticlockwise, the samples showed better friction and wear behavior than when the pin rotated clockwise. These results can provide important guidance for the optimization of the design of heavy-load brake systems and other similar applications.